Future population exposure to Australian heatwaves - Nidhi Nishant; Fei Ji; Yuming Guo; Nicholas Herold; Donna Green; Giovanni Di Virgilio; Kathleen Beyer; Matthew L Riley; Sarah Perkins-Kirkpatrick (Environmental Research Letters, 2022)
Heatwaves are Australia’s deadliest natural hazard. Anthropogenic climate change has increased the intensity, frequency and duration of heatwaves over Australia in the past several decades and these trends are projected to worsen in the future. Despite the strong knowledge of heatwave characteristics and their projected changes, there remains a gap in understanding how the Australian population will be exposed to future heatwaves. This study estimates changes in future exposure to heatwaves over Australia. We find that both for continental Australia and its capital cities, the trends in exposure are not projected to increase, but accelerate in the future. For RCP4.5-SSP2 and RCP8.5-SSP5 scenarios, the mean exposure to heatwaves in Australia is projected to increase by ∼29 and ∼42 times by the end of 21st century. Sydney, Melbourne, and Adelaide are the major cities where the population is most exposed to future heatwaves, with this exposure projected to increase by 52, 61, and 56 times respectively under the RCP8.5-SSP5 scenario. The results demonstrate that anthropogenic climate change is the key contributor (over 95%) in enhancing future heatwave exposure and population change on its own plays a relatively minor role (less than 5%). The results of this study are crucial for planning where adaptation measures might be necessary to protect large group of vulnerable Australians to future heatwave exposure.